Practical reasoning - Audi, Robert (Problems of philosophy (Routledge (Firm)), 1989)
Sets out an original theory of what practical reasoning is and how it bears on the explanation and rationality of human actions. This book should be of interest to students and lecturers of philosophy, especially on human action.